إعداد كراسة التدريبات لكتاب "النحو الواضح" على أساس مهارة التفكير العليا للصف الأول المتوسطة بمعهد الأم مالانج: Preparing of Student Worksheet for Book "al-Naḥwu al-Wāḍiḥ" on The Basis of The Higher Order Thinking Skill for The First Intermediate Grade at Boarding School Al-Umm Malang. - Sarah Iffah Nabillah; Ahmad Mubaligh; Laily Fitriani; Sahrul Muhamad; Indah Rahmayanti (Journal of Arabic Language Teaching, 2025)
The urgent need for Arabic grammar (nahwu) teaching materials that stimulate Higher Order Thinking Skills (HOTS) motivates this study. Previous studies have focused on fundamental cognitive aspects without systematically integrating HOTS into student worksheets (LKS), creating a significant gap, especially for Islamic boarding schools. This research and development (R&D) study used the ADDIE model. Data were collected through classroom observations, interviews, and questionnaires at Al-Umm Malang Islamic Boarding School. Qualitative and quantitative data analysis were employed, and product validation involved subject matter and media experts. The developed HOTS-based student worksheet for "al-Nahwu al-Wadih" received excellent validation scores: 93.3% from content/language experts and 83% from media experts. A paired t-test showed a significant improvement in student learning outcomes (Sig. 0.000 < 0.05), confirming the product's effectiveness. The HOTS-based worksheet is valid, practical, and effective in improving students' understanding of Arabic grammar and critical thinking skills, offering an innovative solution to enhance nahwu learning. الدافع لهذه الدراسة هو الحاجة الملحة لمواد تعليم النحو العربي القادرة على تحفيز مهارات التفكير العليا. ركزت الدراسات السابقة على الجوانب المعرفية الأساسية دون دمج منهجية مهارات التفكير العليا في أوراق عمل الطلاب، مما خلق فجوة بحثية، خاصة في بيئة المعاهد الداخلية. استخدم هذا البحث منهج البحث والتطوير بنموذج ADDIE. تم جمع البيانات من خلال الملاحظات الصفية والمقابلات والاستبيانات في معهد الأم مالانج. استخدم تحليل البيانات النوعي والكمي، وشارك في التحقق من المنتج خبراء في المادة ووسائل الإعلام.  حصلت كراسة التدريبات المطورة القائمة على مهارات التفكير العليا لكتاب "النحو الواضح" على تقييم ممتاز: 93.3% من خبراء المحتوى واللغة و83% من خبراء التصميم. أظهر اختبار ت الزوجي تحسنا ذا دلالة إحصائية في نتائج تعلم الطالبات (0.000 < 0.05 Sig.)، مما يؤكد فعالية المنتج. كراسة التدريبات القائمة على مهارات التفكير العليا صالحة وعملية وفعالة في تحسين فهم قواعد اللغة العربية ومهارات التفكير النقدي لدى الطالبات، مما تقدم حلاً مبتكرًا لتعزيز تعلم النحو.